Metallothionein modulation in relation to cadmium bioaccumulation and age-dependent sensitivity of Chironomus riparius larvae - Toušová, Zuzana; Kuta, Jan; Hynek, David; Adam, Vojtěch; Kizek, René; Bláha, Luděk; Hilscherová, Klára (Environmental science and pollution research international, 2016)
The goal of this study was to contribute to understanding of the mechanisms behind sensitivity differences between early and late instar larvae of Chironomus riparius and to address the influence of the differences in standard testing approaches on the toxicity evaluation. A 10-day contact sediment toxicity test was carried out to assess sensitivity to cadmium exposure in relation to different age and laboratory culture line origin of test organisms. Chironomid larvae of early (OECD 218 method) and late instar (US-EPA600/R-99/064 method) differed substantially in sensitivity of traditional endpoints (OECD: LOEC 50 and 10 μg Cd/g dry weight (dw); US-EPA: LOEC > 1000 and 100 μg Cd/g dw for survival and growth, respectively). Bioaccumulated cadmium and metallothioneins (MTs) concentrations were analyzed to investigate the role of MTs in reduced sensitivity to cadmium in late instar larvae. Metallothioneins were induced after treatment to greater Cd concentrations, but their levels in relation to cadmium body burdens did not fully explain low sensitivity of late instars to cadmium, which indicates some other effective way of detoxification in late instars. This study brings new information related to the role of MTs in age-dependent toxicant sensitivity and discusses the implications of divergence in data generated by chironomid sediment toxicity tests by standardized methods using different instars.
Keywords: Cadmium; larva; Chironomus; Larva; kadmium; Bioaccumulation; Toxicity Tests; Artificial sediment; testy toxicity; Environmental Exposure; metalothionein; Chironomidae; Metallothionein; vystavení vlivu životního prostředí; Animals; zvířata